Analisis fenomena eksploitasi anak perspektif HAM dan Syariah - Safira, Salwa (Maliki Interdisciplinary Journal, 2024)
Children are the determinants of history, the golden generation, and the successors of the nation's ideals. Therefore, in Indonesia there are special regulations regarding the protection of children's rights. Even though there are regulations, in reality there are still many individuals who exploit children. This research aims to find out what is the background to the phenomenon of child exploitation. Then the researcher will try to analyze the case example in Banda Aceh and look at it from a human rights and Sharia perspective. The type of research used is juridical-empirical with a research focus on one case in Banda Aceh. The research results show that there are still practices of child exploitation so there is a gap between implementation and regulations regarding child protection. It is hoped that the results of this research will raise awareness among law enforcers to be more assertive in enforcing the law so that they can handle cases of child exploitation. Apart from government officials, the public also needs to know about this emergency problem so that they are no longer ignorant and participate in efforts to overcome the problem of child exploitation.